2019
DOI: 10.1534/genetics.118.301901
|View full text |Cite
|
Sign up to set email alerts
|

The Role of miRNAs inDrosophila melanogasterMale Courtship Behavior

Abstract: Drosophila melanogaster courtship, although stereotypical, continually changes based on cues received from the courtship subject. Such adaptive responses are mediated via rapid and widespread transcriptomic reprogramming, a characteristic now widely attributed to microRNAs (miRNAs), along with other players. Here, we conducted a large-scale miRNA knockout screen to identify miRNAs that affect various parameters of male courtship behavior. Apart from identifying miRNAs that impact male–female courtship, we obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 84 publications
(130 reference statements)
0
4
0
Order By: Relevance
“…Besides genetic diversity, developmental 50,51 , maternal 52,53 and epigenetic effects 41,54,55 , as well as social interactions 56 , are all thought to contribute to such variation. Recently, microRNAs (miRNAs) have been shown to play a role in regulating some behaviors in Drosophila 5759 and zebrafish 60 , potentially providing another source of behavioral variation. Despite this, variation among individuals is often overlooked when behavior is quantified as averages with associated distributions 24,27–30 .…”
Section: Discussionmentioning
confidence: 99%
“…Besides genetic diversity, developmental 50,51 , maternal 52,53 and epigenetic effects 41,54,55 , as well as social interactions 56 , are all thought to contribute to such variation. Recently, microRNAs (miRNAs) have been shown to play a role in regulating some behaviors in Drosophila 5759 and zebrafish 60 , potentially providing another source of behavioral variation. Despite this, variation among individuals is often overlooked when behavior is quantified as averages with associated distributions 24,27–30 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous work showed that miR-263b plays an important role in the Drosophila peripheral nervous system, where it forms part of a gene regulatory pathway that represses apoptosis during sense organ development (Hilgers, et al 2010); other studies report that downregulation or mutation of miR-263b lead to distortions of adult locomotion patterns (Donelson, et al, 2020) or affects stereotypical parameters of male-female courtship (Iftikhar et al, 2019), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…miRNA locus miR‐iab 4/8, along with the Hox gene Ultrabithorax, has been reported to affect the self‐righting behavior in the morphologically distinct larval as well as adult stages of Drosophila melanogaster (Issa et al, 2019; Picao‐Osorio et al, 2015). miRNAs also regulate many larval neuronal functions and dynamically complex male courtship behaviors in Drosophila (Iftikhar et al, 2019; Klann et al, 2021). Several studies report miRNAs, including miR‐323a, miR‐26a‐3p, miR‐34, miR‐135a, and miR‐101a, which target mRNAs functioning in different brain regions, affecting pathways culminating in anxiety or depression‐like symptoms in model organisms (Cohen et al, 2017; Fiori et al, 2021; Haramati et al, 2011; Li et al, 2021; Mannironi et al, 2018).…”
Section: Mechanisms Of Non−coding Rnas In Behavioral Pathwaysmentioning
confidence: 99%